2021
DOI: 10.48550/arxiv.2106.09167
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Generalization of waving-plate theory to multiple interacting swimmers

Abstract: Early research in aerodynamics and biological propulsion was dramatically advanced by the analytical solutions of Theodorsen, von Kármán, Wu and others. While these classical solutions apply only to isolated swimmers, the flow interactions between multiple swimmers are relevant to many practical applications, including the schooling and flocking of animal collectives. In this work, we derive a class of solutions that describe the hydrodynamic interactions between an arbitrary number of swimmers in a two-dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Experiments and numerical simulations of self-propelled flapping wings and plates (Becker, Masoud, Newbolt, Shelley, & Ristroph, 2015;Newbolt, Zhang, & Ristroph, 2019;Ramananarivo, Fang, Oza, Zhang, & Ristroph, 2016) indicate that orderly formations in schools may emerge simply through flow interactions, and that hydrodynamic mechanisms may be enough to support a group's collective motion. These, along with other studies (Baddoo, Moore, Oza, & Crowdy, 2021;Kurt et al, 2021;Lin et al, 2019), have investigated the stability of spatial configurations of such schooling systems via experimental measurements and/or numerical predictions of hydrodynamic forces. Kurt et al (2021) and Peng et al (2018) have shown propensity for a stable side-by-side configuration in pitching airfoils and plates, while Newbolt et al (2019) and Lin et al (2019) provide evidence of stable configurations in two hydrofoils swimming in tandem.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments and numerical simulations of self-propelled flapping wings and plates (Becker, Masoud, Newbolt, Shelley, & Ristroph, 2015;Newbolt, Zhang, & Ristroph, 2019;Ramananarivo, Fang, Oza, Zhang, & Ristroph, 2016) indicate that orderly formations in schools may emerge simply through flow interactions, and that hydrodynamic mechanisms may be enough to support a group's collective motion. These, along with other studies (Baddoo, Moore, Oza, & Crowdy, 2021;Kurt et al, 2021;Lin et al, 2019), have investigated the stability of spatial configurations of such schooling systems via experimental measurements and/or numerical predictions of hydrodynamic forces. Kurt et al (2021) and Peng et al (2018) have shown propensity for a stable side-by-side configuration in pitching airfoils and plates, while Newbolt et al (2019) and Lin et al (2019) provide evidence of stable configurations in two hydrofoils swimming in tandem.…”
Section: Introductionmentioning
confidence: 99%